The Impact of Digital Transformation on Accounting Measurement in Private Banks.: Dampak Transformasi Digital terhadap Pengukuran Akuntansi di Bank Swasta - Thaer Najm Kadhim (Indonesian Journal of Law and Economics Review, 2026)
General Background: The rapid advancement of digital technologies has significantly transformed business environments and organizational processes. Specific Background: In accounting, digital transformation involves the integration of technologies such as cloud computing, artificial intelligence, and data analytics into financial systems. Knowledge Gap: Despite extensive technological adoption, limited studies comprehensively examine how multiple digital tools collectively reshape accounting practices. Aims: This study aims to analyze the role of digital transformation in redefining accounting systems and professional practices. Results: The findings indicate that digital technologies streamline accounting processes, improve data management, and support more efficient financial reporting. The integration of various digital tools also changes the role of accounting professionals toward more analytical functions. Novelty: This study provides an integrated perspective by combining multiple technological dimensions within a single analytical framework of accounting transformation. Implications: The results highlight the need for organizations to adopt structured digital strategies and develop competencies to adapt to evolving accounting environments. Keywords: Digital Transformation, Accounting Systems, Cloud Computing, Artificial Intelligence, Financial Reporting Key Findings Highlights Technological integration supports more efficient financial data processing Professional roles shift toward analytical and decision-oriented tasks Combined technological frameworks clarify structural changes in accounting